Proceso atención de enfermería en paciente de 27 años con embarazo molar. - Yánez Fuentes, Juliana Izamar (2021)
Molar pregnancy, also known as hydatidiform mole, is defined as a rare complication of pregnancy characterized by abnormal growth of trophoblasts, which are responsible for giving rise to the formation of the placenta. It is known that there are two types of molar pregnancies: the complete and the partial, the first is that cell that is formed abnormally, in the form of fluid-filled cysts, the second are characterized by presenting a fetus, but without the possibility of survival In these two types of cases, a spontaneous abortion always occurs early in the first trimester of pregnancy.The main cause for a molar pregnancy is due to abnormal fertilization, the placenta will grow normally, but without the presence of a fetus or with the presence of a fetus in the form of a cyst, an ultrasound can confirm this pathology of a woman, in which you will see some granules that represent the morula. The present clinical case study was carried out in the nursing care process in a 27-year-old patient with a history of urinary infection who attended the Martin Icaza General Hospital, due to moderate bleeding with abdominal pain of 12 hours of evolution, who in turn evolved adequately thanks to the interventions carried out by health personnel.